Effective removing of hexavalent chromium from wasted water by triboelectric nanogenerator driven self-powered electrochemical system – Why pulsed DC is better than continuous DC?. (October 2019) - Zhou, Linglin; Liu, Di; Li, Shaoxin; Yin, Xing; Zhang, Chunlei; Li, Xinyuan; Zhang, Chuguo; Zhang, Wei; Cao, Xia; Wang, Jie; Wang, Zhong Lin
Abstract: Electrochemical techniques have been extensively applied to treat heavy metal pollution in our daily life. Traditional electrochemistry is always driven by continuous DC (CDC), but the energy harvested in environment from water using nanogenerator is always a pulsed DC (PDC). The question is if the CDC has a better performance than PDC? Here, we systematically investigated the electrochemical performance of hexavalent chromium (Cr(VI)) removal from wasted as powered by pulsed output of triboelectric nanogenerator (TENG) using the energy harvested from environment. By optimizing the frequency and on-off ratio of PDC, the removal efficiency of Cr(VI) can be maximally enhanced by 53.5% compared to that driven by a CDC under equal amount of electric charges, which is further confirmed by electrochemical experiments driven by layered TENG. The reason is the more production of Fe 2+, the better utilization of Fe 2+, and the higher ion diffusion rate during the process driven by PDC, where the electrode passivation caused by concentration polarization of the anode region and over potential is reduced. Besides, a self-powered system is designed for removing contaminant from wastewater by harvesting energy from the flowing water through rotary-TENG, where heavy metal pollutant such as Cr(VI) can be sufficiently and continuously removed. This study demonstrate the feasibility and effectiveness of self-powered electrochemical for cleaning environment pollution using the harvested energy. Graphical abstract: A self-powered system with a pulsed DC output is used to remove Cr(VI) by harvesting energy from the flowing water through rotary-TENG for improving the removal efficiency of Cr(VI) and solving the extra power supply during electrochemical treatment.Image 1 Highlights: Our findings establish optimization methodologies for electrochemical removing Cr (VI). A substantial improvement of electrochemical performance for removing Cr(VI) is achieved through using PDC. Electrochemical reaction powered by TENG with pulse signal exhibits a higher removal efficiency than that of CDC. A self-powered system based on TENG is fabricated to remove Cr(VI), which greatly lower the power consumption. A promising application of the self-powered system is provided for energy saving and environmental governance.